PENGGUNAAN JERAMI BUNGA SEDAP MALAM TERFERMENTASI DALAM COMPLETE FEED TERHADAP PERFORMA DOMBA LOKAL - Suryanto, Dedi; Marthotillah, Achmad Bagus A.; Ali, Usman (BUANA SAINS, 2023)
This study aimed to assess the impact of fermented night-blooming jasmine straw (JBSMF) in complete feed on local sheep performance, including feed intake, weight gain, feed digestibility, and feed efficiency. Materials included male local sheep, rice bran, concentrate, pollard, corn stover, premix, and JBSMF. The research was conducted on KTHRI in Wagir Village, Sukun, Malang and used the randomized block design experiment featured four treatment, P0 = control feed, P1 = 10% dry JBSMF, P2 = 20% JBSMF, and P3 = 30% JBSMF in complete feed, each repeated three times. Observed variables encompassed sheep production performance: feed intake, weight gain, feed digestibility, and feed efficiency. Results indicated that JBSMF in complete feed had no significant impact on local sheep performance. The optimal treatment was 30% JBSMF inclusion. In conclusion, increasing fermented JBSMF in dry form in complete feed showed the potential to enhance local sheep performance and optimal use of 30 % of dry JBSMF .